Tales of boundary spanning for climate actions in cities: from theory to practice, and back - Sareh Moosavi; Bridget Keane; Debra Roberts; Jorn Verbeeck; Sarah Bell; Cathy Oke (npj Urban Sustainability)
Abstract Effective climate actions in cities require integrating knowledge into actionable policy and practice. This perspective article provides empirically grounded insights on different roles, practice challenges and impacts of boundary spanners in mediating the science, policy and practice knowledge universes, by drawing upon critical self-reflections of four boundary spanners. It offers important insights into existing challenges they face in practice, and highlights opportunities for supporting them in accelerating climate actions.